2015
DOI: 10.1093/ejcts/ezv403
|View full text |Cite
|
Sign up to set email alerts
|

The effects of an intentional transition from extrapleural pneumonectomy to extended pleurectomy/decortication

Abstract: The transition from EPP to EPD in our standard practice has enabled us to operate on more elderly, frail patients with no significant increase in use of hospital resources, and without detriment to overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 18 publications
4
36
0
Order By: Relevance
“…can be applied to a wider cohort of patients due to its lower detrimental effect and mortality rate, without affecting long term results [49].…”
Section: Which Approach For Radical Surgery?mentioning
confidence: 99%
See 1 more Smart Citation
“…can be applied to a wider cohort of patients due to its lower detrimental effect and mortality rate, without affecting long term results [49].…”
Section: Which Approach For Radical Surgery?mentioning
confidence: 99%
“…More recently, Lang-Lazdunski [48] published the results of a multimodality approach using EPD for MPM; one hundred and two patients had a median survival of 32 months and a 2-year survival of 62.9%; when observing restricted groups of patient N0 or with epithelioid histology 2-year survival was 66.7% and 76,5%respectively. Concurrently, in a report comparing EPP and EPD performed in a single institution, Sharkey[49] reported outcomes of 358 patients; the EPD population had a median survival of 12.3 months, while for patients treated with EPP it was 12.9 months; when calculated for patients with epithelioid, node-negative disease, survival was significantly higher accounting for 24.2 months and 20.7 months respectively.Furthermore, an increasing interest in biomarkers as prognostic factors is developing. White blood cells count, LDH, PCR levels, NLR (Neutrophil/Lymphocytes ratio), PLR (Platelet/Lymphocytes Ratio), albumin levels and hemoglobin levels have been related to prognosis, but their clinical application is still unestablished[50,51].…”
mentioning
confidence: 99%
“…[1][2][3][4] However, lung-sparing pleurectomy-decortication (P/D) is increasingly a preferred surgical approach for MPM. 5,6 Safe delivery of cytotoxic radiation to the hemithorax with two intact radiosensitive lungs is challenging. Conventional matched photonelectron radiation techniques are insufficiently able to spare the underlying ipsilateral lung, so the techniques result in excess toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Initially P/D was considered only palliative, but during the decades its role was redefined and this type of surgery gained an important position as a radical surgery. Recent studies have shown that survival time after EPP and P/D is similar, while mortality and morbidity are higher post EPP (24,40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Preservation of the underlying lung seems to guarantee a lower mortality and morbidity rate: Cao et al reported a perioperative mortality of 2.9% (vs. 6.8% of EPP) and morbidity of 27.9% (vs. 62% of EPP) (15), Flores showed a mortality and morbidity rate of 4% (vs. 7% of EPP) and 6.4% (vs. 10% of EPP) respectively (22). Several authors also insisted on the importance of a case-by-case patient's characteristics evaluation: the EPP and P/D should not be considered as alternative approaches (22,23) and P/D could be used in a greater number of patients because of its lower mortality and morbidity rate, with similar long-term survival rate (24).…”
Section: Discussionmentioning
confidence: 99%